Is Identity a Relation? - Švob, Goran (Array, 1999)
Our question was actually the starting point of Freges famous article on sense and reference. Freges answer was not quite straightforward, since he quickly shifted from the question on nature of identity to the discussion of meaning of singular terms. Yet he seemed to hold the view of identity as a relation of an object to itself. There was, however, another account of identity, given by Frege earlier, in his Begriffsschrift. There he talked of identity as a relating to names and not to what the names signify. The view that identity should be relation between objects, or more precisely, between every object and itself, was sharply criticised by Wittgenstein who even suggested that the very sign of identity should not be part of logically perfect language. This idea was later investigated in works of Carnap and Hintikka, and it was shown by both authors how one could construct logical languages without the sign of identity. Still, both of them held to the principle of tolerance in syntax and would not go further into the question of the real nature of identity. Nowadays, the idea of objects being (necessarily, for that matter) identical to themselves, and this identity being part of their logical or metaphysical nature, seems to be spreading again, as if nothing had happened. There seems to be at work constant fusion of two senses of identity, one of them being conceived as an imperfect version of the other. First of all, there is the usual, commonsense, notion of identity as impossibility of distinguishing several individuals. This notion goes well together with the notion of indiscernibility and mutual substituivity, the latter being taken quite literally. Then there is the other notion, of so called strict identity. Taking indiscernibility over to this notion results in various nonsensical statements and pseudophilosophical puzzles. Namely, for an object to be indiscernible from another, presupposes possibility of comparison and, as Wittgenstein liked to stress, it is not at all clear how one could compare an object to itself. As for the mutual substituivity, it is quite obvious that in this context it means possibility of substitution of terms, not of objects. For proper analysis of strict identity, early Freges suggestion seems to be more adequate. Though one could not, of course, simply talk of identity as a relation between names, one could tackle the problem by treating identity as a complex semantical (or, maybe, epistemological) relation, involving using various terms for single object (or, recognizing an object known from a certain aspect, now given in another aspect), and not simply as a relation between objects, i.e. between every object and itself.